Capsular bag distension syndrome following phacoemulsification with implantation of intraocular lens - Eng, KJ; Malisa A,; Safinaz Mohd Khialdin, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Capsular bag distension syndrome is a rare complication following phacoemulsification with posterior chamber intraocular lens implantation. We describe the case of a middle-age male, who developed early onset capsular bag distension syndrome of the right eye after phacoemulsification with implantation of plate haptic posterior chamber intraocular lens (Zeiss CT ASPHINA 509MP). There was persistent poor vision during follow up at 1 week and 5 weeks post-surgery with a myopic shift of 2.5 diopters sphere (DS). The intraocular pressure was only elevated at 2 hours post-operative and was normal during the subsequent followup. Distension of capsular bag was confirmed with the IOP Master 700 which showed abnormal separation of posterior capsule from the intraocular lens. He was diagnosed with capsular bag distension syndrome secondary to retention of viscoelastic. Right eye removal of retained viscoelastic was performed and the capsular bag distension syndrome resolved successfully with best corrected visual acuity at 6/6. Hence, complete clearance of viscoelastic during phacoemulsification with plate haptic intraocular lens is important in order to prevent capsular bag distension syndrome.